If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 1200 + 4x = 360x Solving 1200 + 4x = 360x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-360x' to each side of the equation. 1200 + 4x + -360x = 360x + -360x Combine like terms: 4x + -360x = -356x 1200 + -356x = 360x + -360x Combine like terms: 360x + -360x = 0 1200 + -356x = 0 Add '-1200' to each side of the equation. 1200 + -1200 + -356x = 0 + -1200 Combine like terms: 1200 + -1200 = 0 0 + -356x = 0 + -1200 -356x = 0 + -1200 Combine like terms: 0 + -1200 = -1200 -356x = -1200 Divide each side by '-356'. x = 3.370786517 Simplifying x = 3.370786517
| (x/(x+2))+(4/(x+1))=1 | | (x/x+2)+(4/x+1)=1 | | 4-3(3-N)=3(2-5N) | | a^2=-7a | | (x/x+2)+(4/x+x)=1 | | 1996+43x=(3200) | | 7385-67(3200)= | | -7.8=-1.4+y/4 | | 5(x-2)=9x-3(2x-4) | | 3(x+2.55)=2x | | 1996+43x=32 | | 9x+9.84=5x+17 | | X^2+4x-3840=0 | | 16p*9p= | | 5x^2+31x=28 | | 2/27(3^7-8x7+2) | | 44=-4+6m | | 9/3(6x4/8)=x | | (-7a^3b^2)(4ab-a^2b^2)=0 | | y-45=-8/7(x-20) | | 3t-7=5t*6t | | (5x)/6+(x-4)/3=13/6 | | y=8+(-4/3)x | | 6k=115 | | g+3=16 | | 3x-5=4x+0.5(8x-6) | | 2/3r=18 | | 12=y/3 | | w+5=25 | | 88=11p | | 3=j-9 | | 12/2/3 |